COHESIVE DEVICES IN NOVEL “GONE GIRL‟ BY GILLIAN FLYNN - Ni Komang Novita Dewi; Yohanes Kristianto (LPPM Universitas Dhyana Pura, 2016)
ABSTRACTThis paper entitled Cohesive Devices in Novel “Gone Girl”. This study concerns with the typesof cohesive devices occur in the novel and the meaning of cohesive devices that found in thenovel. The aims of this paper are to know the types of cohesive devices found in the novel andto find out the meaning of cohesive devices that found in the novel. The cohesive devices weretaken from the documentation method and library research. In completing the process ofcollecting the data, note taking technique was applied. The collected data were analyzeddescriptively. The data for this study belongs qualitative data. The main theory used in this paperwas theory of cohesion by Halliday and Hassan in their book “Cohesion in English” (1976).Besides. The finding showed the four types of cohesive devices proposed by Halliday andHassan, those are: 22 references, 6 substitutions, 43 conjunctions and 20 lexical cohesion occurin this study. The most dominant type of cohesive devices was conjunction because the novelconsist of many clauses so that needs to use many conjunction and the writer would like toconnect ideas within the text to make the readers easy to understand. Then the writer would liketo make that novel more interesting for the readers.Keywords: cohesion, cohesive devices, novelABSTRAKJudul penulisan ini adalah “Cohesive Devices in Novel “Gone Girl”. Penulisan ini mengenaitipe-tipe alat kohesif yang terdapat didalam novel dan makna dari alat-alat kohesif yangditemukan didalam novel. Tujuan dari penulisan ini adalah untuk mengetahui tipe-tipe alatkohesif yang ditemukan dalam novel dan untuk menemukan makna dari alat-alat kohesif yangditemukan dalam novel. Alat kohesif diambil dengan cara mengumpulkan data, yaitu mencatat.Pengumpulan data dianalisa secara deskriptif, data dalam penulisan ini termasuk datakualitatif. Teori utama yang dipakai dalam penulisan ini adalah teori tentang kohesi olehHalliday dan Hassan dalam buku mereka yang berjudul “Cohesion in English” (1976). Selainitu, dalam penulisan ini ditemukan 4 tipe-tipe alat kohesi berdasarkan teori dari Halliday danHassan, yaitu; 22 referensi, 6 substitusi, 43 konjungsi dan 20 kohesii leksikal. Dalam penulisanini, yang paling dominan adalah konjungsi karena novel ini terdapat banyak kalimat, sehinggaoleh karena itu diperlukan banyak konjungsi dan penulis ingin menggabungkan pemikirandengan teks sehingga para pembaca mudah untuk memahaminya. Kemudian penulis juga inginmembuat novel tersebut lebih menarik bagi para pembaca.Kata kunci: kohesif, alat kohesif, novel